Biodiversity How-To Guide 3: Defining Outcomes & Indicators for Monitoring, Evaluation, and Learning in USAID Biodiversity Programming (USAID, 2016)
The Biodiversity How-To Guide 3: Defining Outcomes and Indicators for Monitoring, Evaluation, and Learning in USAID Biodiversity Programming is the third in a series of three guides that provide in-depth guidance on key tools and practices to support design teams as they design and manage biodiversity programs within the Program Cycle and in accordance with the USAID Biodiversity Policy. It uses the results chains developed in the second guide and provides help identifying key results for developing outcome statements and indicators, as required by USAID’s Biodiversity Code, updated in the Biodiversity Policy.